A self-tracking study of international students in France: Exploring opportunities for language and cultural learning. Issue 3 (19th June 2019) - Guichon, Nicolas
Abstract: This exploratory study focuses on international students' usage of digital tools in order to understand what role such tools play in the transition to their new academic environments and what learning opportunities they provide. Not only do digital tools accompany international students' social, cultural, and linguistic transitions as they move to France to further their language competence, but their usage also reveals part of the social and semiotic adjustments they have to make in the process. Sixteen international students who volunteered for the study were given a smartphone application with which they could track learning opportunities by taking pictures and writing textual commentaries. The data, collected over a period of five weeks, thus include the resulting entries these participants shared in their mobile multimodal diaries with the researchers, as well as an end-of-project debriefing that was conducted to shed further light on the international students' digital habits and their attitudes towards self-tracking. This study indicates that digital tools can play an important and pervasive role in facilitating international students' linguistic development and their dealings with everyday life abroad. It also confirms that self-tracking apps can be instrumental in enhancing students' awareness of learning opportunities outside the classroom.